Diagnostic monitoring of solid particle erosion in steam turbines - Bellanca, C.P. (IEEE transactions on energy conversion, 1988)
An in situ wear measurement system has been demonstrated for steam turbine applications. The diagnostic technique can measure the wear and erosion damage caused by solid particle erosion (SPE) on a main steam stop valve bypass valve disc (SVBV). The technique consist of weakly activating the areas on the disc subject to wear by placing the disc in an ion accelerator beam. The induced radionuclides emit specific gamma rays in strengths safe for personnel, but strong enough for detection. The change in activity can be accurately correlated to the amount of erosion. The results of the field testing and associated economic evaluation indicate that the erosion monitoring system will allow Dayton Power and Light to plan SVBV disc replacement intervals based on actual measured erosion rates.< >